Genetic variation in male attractiveness: It is time to see the forest for the trees. (1st April 2016) - Prokop, Zofia M.; Drobniak, Szymon M.
Abstract: Female choice based on multiple male traits, rather than on any single one, has been reported in many species and may well be a rule rather than an exception. However, the implications this has for selection acting on choosiness itself remain underappreciated. We argue that this constitutes one of the important impediments to our understanding of the evolution of mate choice. We discuss this issue primarily in the context of the Fisherian model of sexual selection. We review theory and empirical data, showing how the crucial parameter of the model—genetic variation in male attractiveness—can be estimated when attractiveness is a function of multiple traits. Based on the reviewed theory, we show how relying on individual male traits, instead of overall attractiveness, can produce biased estimates of Fisherian benefits of female choice. This bias can be substantial, especially when many traits contribute to male attractiveness. We discuss a number of methodological issues that, we hope, will stimulate future studies and help resolving the long‐standing mystery of mate choice.